Modular Evolution and Population Variability of Oikopleura dioica Metallothioneins - Calatayud, Sara; Garcia-Risco, Mario; Capdevila, Mercè; Cañestro, Cristian; Palacios, Òscar; Albalat, Ricard (Frontiers in Cell and Developmental Biology, 2021)
Chordate Oikopleura dioica probably is the fastest evolving metazoan reported so far, and thereby, a suitable system in which to explore the limits of evolutionary processes. For this reason, and in order to gain new insights on the evolution of protein modularity, we have investigated the structure, function and evolution of multi-modular metallothionein (MT) proteins in O. dioica. MTs are a heterogeneous group of modular proteins defined by their cysteine (C)-rich domains, which confer the capacity of coordinating different transition metal ions. O. dioica has two MTs, a bi-modular OdiMT1 consisting of two domains (t-12C and 12C), and a multi-modular OdiMT2 with six t-12C/12C repeats. By means of mass spectrometry and spectroscopy of metal-protein complexes, we have shown that the 12C domain is able to autonomously bind four divalent metal ions, although the t-12C/12C pair –as it is found in OdiMT1– is the optimized unit for divalent metal binding. We have also shown a direct relationship between the number of the t-12C/12C repeats and the metal-binding capacity of the MTs, which means a stepwise mode of functional and structural evolution for OdiMT2. Finally, after analyzing four different O. dioica populations worldwide distributed, we have detected several OdiMT2 variants with changes in their number of t-12C/12C domain repeats. This finding reveals that the number of repeats fluctuates between current O. dioica populations, which provides a new perspective on the evolution of domain repeat proteins.